2018
DOI: 10.1002/hyp.13243
|View full text |Cite
|
Sign up to set email alerts
|

Insights into groundwater salinization from hydrogeochemical and isotopic evidence in an arid inland basin

Abstract: In the Manas River basin (MRB), groundwater salinization has become a major concern, impeding groundwater use considerably. Isotopic and hydrogeochemical characteristics of 73 groundwater and 11 surface water samples from the basin were analysed to determine the salinization process and potential sources of salinity.Groundwater salinity ranged from 0.2 to 11.91 g/L, and high salinities were generally located in the discharge area, arable land irrigated by groundwater, and depression cone area. The quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 56 publications
(60 reference statements)
1
19
0
Order By: Relevance
“…In the USA, increasing efforts are now made to delineate brackish groundwater resources to strategically deploy desalination systems there to augment drinking-water supplies as freshwater sources become increasingly scarce (Chowdhury et al, 2018). Groundwater salinity is of mounting concern in many semi-arid systems globally (Boukhari et al, 2018;Liu et al, 2018), and may be increasingly exacerbated by the impacts of irrigated agriculture (Foster et al, 2018). Salinity within shallow or intermediate depth groundwater is considered high over 16% of the global land area, within which some 1.1 billion people reside (Van Weert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In the USA, increasing efforts are now made to delineate brackish groundwater resources to strategically deploy desalination systems there to augment drinking-water supplies as freshwater sources become increasingly scarce (Chowdhury et al, 2018). Groundwater salinity is of mounting concern in many semi-arid systems globally (Boukhari et al, 2018;Liu et al, 2018), and may be increasingly exacerbated by the impacts of irrigated agriculture (Foster et al, 2018). Salinity within shallow or intermediate depth groundwater is considered high over 16% of the global land area, within which some 1.1 billion people reside (Van Weert et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…water, due to strong evaporation in arid areas [33]. Furthermore, the mean isotopes of shallow groundwater (δ 18 O = −8.2‰) were lower than the values of river water but higher than those for the middle groundwater (mean δ 18 O = −9.1‰) and deep groundwater (mean δ 18 O = −9.3‰) in the study area.…”
Section: Stable Water Isotopic Compositionmentioning
confidence: 68%
“…This indicated that river discharge was dominated by precipitation during the wet season [38]. Stable isotopes of reservoir water (mean δ 18 O = −6.1‰) were higher than those of river water, due to strong evaporation in arid areas [33]. Furthermore, the mean isotopes of shallow groundwater (δ 18 O = −8.2‰) were lower than the values of river water but higher than those for the middle groundwater (mean δ 18 O = −9.1‰) and deep groundwater (mean δ 18 O = −9.3‰) in the study area.…”
Section: Stable Water Isotopic Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…The elevation of the basin descends from 5243 m above sea level (a.s.l.) in the mountains to 256 m in the plains (Cheng et al, 2006; Liu et al, 2018).…”
Section: Methodsmentioning
confidence: 99%